Role of Platelet-Rich Plasma in Spinal Fusion Surgery: Systematic Review and Meta-Analysis - Daudi R. Manini; Frank D. Shega; ChaoFeng Guo; YuXiang Wang (Advances in Orthopedics)
Background. Platelet-rich plasma (PRP) has been used very successfully in enhancing bone fusion in animal experiments. Also, the efficaciousness of PRP in other specialties of medicine such as dentistry, dermatology ophthalmology, and sports medicine is well documented. But the use of PRP to augment bone fusion after spinal surgery in humans is still controversial. We conducted a meta-analysis to determine the role of PRP in enhancing spinal fusion by fastening the rate of new bone formation and decreasing pain after spinal surgery in humans. Methods. We searched PubMed, EMBASE, and the Cochrane Library studies that compared PRP versus control in enhancing spinal fusion after deformity correction. Results. Five retrospective studies with 253 participants and nine prospective cohort studies with 460 participants were identified. The bone fusion rate was excellent for studies that used a high platelet concentration in PRP relative to control (odds ratio (OR) = 4.35, 95% confidence interval (CI) (2.13, 8.83), and P<0.05) while bone fusion was poor to studies that used a low concentrate of platelet in PRP relative to control. The rate of new bone formation was high in the PRP group compared to the control group with the mean difference in Hounsfield unit (HU) 144.91 (95% CI (80.63, 209.18), P<0.05). Time to bone fusion was short in the PRP group during the first six months of surgery relative to the control group with a mean difference of −2.03 (95% CI (−2.35, −1.7); P<0.05). No difference was found in pain reduction by visual analog score (VAS) between the PRP group and control. Conclusion. PRP facilitates new bone formation and bone fusion with a minimum concentration of the growth factor 5 times that of the peripheral blood. PRP stimulatory effects are not continuous and are very effective within six months of implantation.